Brain drain from Turkey: an investigation of students' return intentions - Nil Demet Güngör; Aysit Tansel (Institute for the Study of Labor (IZA), 2006)
The emigration of skilled individuals from Turkey attracted greater media attention and the interest of policymakers in Turkey, particularly after the experience of recurrent economic crises that have led to an increase in unemployment among the highly educated young. This study estimates a model of return intentions using a dataset compiled from an Internet survey of Turkish students residing abroad. The findings of this study indicate that, as expected, higher salaries offered in the host country and lifestyle preferences, including a more organized environment in the host country, increase the probability of student non-return. However, the analysis also points to the importance of prior return intentions and the role of the family in the decision to return to Turkey or stay overseas. It is also found that the compulsory service requirement attached to government scholarships increases the probability of student return. Turkish Student Association membership also increases return intentions. Longer stay durations, on the other hand, decrease the probability of return. These findings have important policy implications.
Keywords: 330; Brain Drain; Studierende; Rückwanderung; Türkei